2017
DOI: 10.18632/oncotarget.15415
|View full text |Cite
|
Sign up to set email alerts
|

Features and risk factors of carotid atherosclerosis in a population with high stroke incidence in China

Abstract: Epidemiological studies have reported associations between traditional cardiovascular risk factors and carotid intima-media thickness (CIMT) or carotid plaque. However, definite risk factors at different phases of carotid atherosclerosis remain controversial. We aimed to explore risk factors and characteristics of carotid atherosclerosis at different stages in a low-income population with a high incidence of stroke in China. Between April 2014 and January 2015, we recruited 3789 stroke-free and cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…Of the studies that excluded people with prior CVDs, the prevalence of carotid plaque was 9.7% in villages in Xinjiang, 17 18.8% in Shanghai city, 18 16.8% to 30.6% in Nanjing city, 19 and 41.5% in a low-income rural community in Tianjin. 20 The reported overall prevalence of CA or increased IMT was from 11.2% in a rural community in Shandong 21 to as high as 40.3% in Shenyang city. 22 Different approaches in participant sampling and selection, ultrasound techniques, and diagnosis criteria may cause such substantial differences in the reported prevalence of CA and carotid plaque, although it is generally impossible to be certain based on published literature.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Of the studies that excluded people with prior CVDs, the prevalence of carotid plaque was 9.7% in villages in Xinjiang, 17 18.8% in Shanghai city, 18 16.8% to 30.6% in Nanjing city, 19 and 41.5% in a low-income rural community in Tianjin. 20 The reported overall prevalence of CA or increased IMT was from 11.2% in a rural community in Shandong 21 to as high as 40.3% in Shenyang city. 22 Different approaches in participant sampling and selection, ultrasound techniques, and diagnosis criteria may cause such substantial differences in the reported prevalence of CA and carotid plaque, although it is generally impossible to be certain based on published literature.…”
Section: Discussionmentioning
confidence: 97%
“…To compare our results with previous studies, we searched PubMed to identify population‐based studies that reported the prevalence of CA detected by ultrasound in China, and summarized findings are shown in Table 4. Of these previous studies,16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26 only the CKB (China Kadoorie Biobank) study included a large sample of participants (N=24 822) from multiple geographic regions in China16; all other studies were geographically local. The CKB study reported that the overall prevalence of carotid plaque was 31%, which was much higher than the prevalence of 13.9% in the present study; however, the CKB study included participants with stroke (5.4%) or coronary heart disease (7.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bilateral extracranial carotid artery trees (including the common carotid artery, carotid sinus, and internal and external carotid arteries) were screened for plaque. Carotid plaque is defined as: (1) local CIMT exceeds 1.5 mm, (2) localized CIMT bulge protrudes into the lumen for more than 0.5 mm, and (3) local CIMT exceeds 50% in the peripheral medial lining; early-stage atherosclerosis was defined as CIMT ≥1 mm (21,22). CIMT at the near and far walls of the common carotid artery was measured on the left and the right, and three values were obtained: maximum CIMT, minimum CIMT, and average CIMT per lateral.…”
Section: Ultrasonography Measurementsmentioning
confidence: 99%
“…Although medication has shown to be effective in preventing cardiovascular events associated with ASCVD 17 , patients may exhibit suboptimal adherence due to the long term management required, disease misperceptions, poor patient-physician relationship, weak social support and comorbidities [18][19][20][21] . The txt2heart trial is an international collaboration evaluating the efficacy and safety of SMS on clinical outcomes and adherence in different countries including Colombia, Ghana, India and Singapore.…”
Section: Introductionmentioning
confidence: 99%